Cycle versus swap strategy after TNFi discontinuation in psoriatic arthritis and axial spondyloarthritis: a quasi-experimental study - Nathan den Broeder; Noortje van Herwaarden; Alfons A den Broeder; Johanna E Vriezekolk; Emmerik F A Leijten; Elien Mahler; Ilse van Es; Lisan de Beijer (RMD Open, 2025)
Objectives To compare a bDMARD mode of action cycle vs swap treatment strategy in patients with psoriatic arthritis (PsA) or axial spondyloarthritis (axSpA) after first tumour necrosis factor inhibitor (TNFi) discontinuation.Methods In December 2019, our local treatment protocol for PsA and axSpA changed from a cycle strategy (first TNFi to second TNFi) to a swap strategy (first TNFi to IL-17i). We performed a retrospective comparison of the 3-year drug retention rate using multivariable Cox regression (ref: cycle group) and disease activity (DAS28-CRP for PsA, BASDAI for axSpA) in patients with a clinical diagnosis of PsA and axSpA. For subgroup analyses, Cox regression models were stratified by sex, reason of first TNFi discontinuation, and (non-)radiographic status in axSpA.Results In PsA patients (n=406), there was no overall significant difference in drug retention between strategies (HR: 1.17 (95% CI: 0.87 to 1.58), p=0.29), but male PsA patients had a significant higher risk for treatment discontinuation following a swap strategy. In axSpA patients (n=335), the swap strategy was overall associated with a higher risk of treatment discontinuation (HR: 1.46 (95% CI: 1.03 to 2.07), p=0.04). Patients who discontinued their first TNFi due to inefficacy and patients diagnosed with radiographic axSpA were at significant higher risk for treatment discontinuation following a swap strategy. No significant differences in disease activity were found for treatment strategies in PsA or axSpA.Conclusion In PsA, the cycle and swap treatment strategy performed similarly, while in axSpA, the cycle strategy was associated with a significant higher drug retention rate.